2015
DOI: 10.1128/aem.01160-15
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Physiology of Acetate Metabolism by the Pta-Ack Pathway of Streptococcus mutans

Abstract: In the dental caries pathogen Streptococcus mutans, phosphotransacetylase (Pta) catalyzes the conversion of acetyl coenzyme A (acetyl-CoA) to acetyl phosphate (AcP), which can be converted to acetate by acetate kinase (Ack), with the concomitant generation of ATP. A ⌬ackA mutant displayed enhanced accumulation of AcP under aerobic conditions, whereas little or no AcP was observed in the ⌬pta or ⌬pta ⌬ackA mutant. The ⌬pta and ⌬pta ⌬ackA mutants also had diminished ATP pools compared to the size of the ATP pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…10 Interestingly, similar observations were also noted in other bacteria, i.e. it was shown that disruption of the pta gene in Escherichia coli 40 and inactivation of the ackA gene in Streptococcus mutans 41 did not cause a substantial loss in the amounts of generated ATP.…”
Section: Discussionsupporting
confidence: 66%
“…10 Interestingly, similar observations were also noted in other bacteria, i.e. it was shown that disruption of the pta gene in Escherichia coli 40 and inactivation of the ackA gene in Streptococcus mutans 41 did not cause a substantial loss in the amounts of generated ATP.…”
Section: Discussionsupporting
confidence: 66%
“…KEYWORDS acid tolerance, carbohydrate metabolism, dental caries, gene regulation, pyruvate E stimates from evolutionary genomic analysis of over 50 isolates of the dental caries pathogen Streptococcus mutans from around the globe (1) are consistent with the bacterial composition of a small number of samples of dental calculus from ancient human fossils; both predict that S. mutans became a significant constituent of human oral biofilms around 3,000 to 10,000 years ago (2, 3), the time when humans adopted hydrate metabolism and in the ability of the organisms to cope with stressors that are commonly encountered in the oral cavity, particularly oxidative stress (30). The Pta-Ack pathway involves Ack-dependent generation of ATP and acetate from acetyl phosphate (AcP), which can be produced from acetyl coenzyme A (acetyl-CoA) and phosphate by Pta.…”
Section: Importancementioning
confidence: 65%
“…In particular, the ilv and leu genes encode the biosynthetic enzymes to convert pyruvate to BCAAs (7). Notably, we showed previously that ilvE (SMU.1203c) expression was downregulated in an ackA mutant, which accumulates AcP levels at much higher levels than the wild-type strain (30). To investigate the interrelationship of the Pta-Ack and BCAA biosynthetic pathways further, we monitored growth of pta and ackA mutant strains in FMC medium with modified BCAA composition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 12 proteins that were differentially expressed in response to both drug treatments were noted to include enolase (SMU.1247), which can be a moonlighting surface-associated protein in S. mutans (Ge et al, 2004), and acetate kinase (SMU.1978), which participates in the Pta-Ack pathway that can influence biofilm formation. (Kim et al, 2015) In conclusion, through this work we were able to establish a potential role of pepX in biofilm development of S.mutans and moved a step forward in the identification and development of novel Sm-DPP IV inhibitors. We have also tried to demonstrate the likely effect of AHD drugs on bacteria, as a proof of the concept that many regularly used drugs may exert some sort of side activity against microbes transiently or permanently inhabiting the human body.…”
Section: Discussionmentioning
confidence: 81%